Pembrolizumab-associated acral necrosis and esophageal necrosis - Austin Thomas; Athira Jayan; Yusuf Chang; Reese Svetgoff; Saumil Datar; Vinayak Memula; Michael Huang; Laura Winikka; Jeffrey Chen (Current Problems in Cancer: Case Reports, 2022)
Immune checkpoint inhibitors (ICIs) have revolutionized the treatment of various advanced malignancies. By unleashing the immune system from its natural self-autoregulating mechanisms, malignant cells throughout the body are more effectively destroyed. These new immunotherapies have been used for a variety of cancers including cancer of the lung, colon, skin, prostate, and more. Although these therapies provide an effective mechanism at treating cancer, they unfortunately come with undesirable autoimmune side effects known as immune-related adverse events (irAEs). Here, we present a unique case of a patient who developed rare irAEs following ICI treatment. The patient was a 60-year-old male with stage IV lung adenocarcinoma who was treated with one dose of maintenance pembrolizumab after gamma radiation and chemotherapy. He subsequently developed acral necrosis requiring digital amputations followed by esophageal necrosis requiring gastrostomy tube placement. Out of concern for ICI-related acral necrosis, he was treated with prednisone, tocilizumab, pentoxifylline, amlodipine, and aspirin. He was readmitted one month later for worsened digital ischemia and received another round of pentoxifylline but unfortunately required digital amputations in the outpatient setting. He was admitted again about one month later for severe ulcerative necrosis of the entire esophagus and restarted on a high-dose prednisone taper for suspected ICI-induced esophageal necrosis. At the latest follow-up, the patient was successfully tapered off steroids and had no recurrent digital ischemia or esophagitis symptoms. As this case highlights, it is critical that providers recognize early symptoms of digital ischemia in patients receiving immunotherapy, and that these patients may be at risk for ischemic events in other body systems, such as the gastrointestinal system. Early cessation of ICIs, aggressive immunosuppression, and supportive measures could potentially lead to both preservation of the digits and GI tract. Further studies of optimal treatment strategies for these rare irAEs are warranted.